Overview of Issues at Stake - (:unkn) unknown (My University, 2007)
The nine official Bantu languages of South Africa, as we are all aware, have all been standardised to a significant extent, and there are clear norms for writers to follow. However, we also know that these standardised varieties have not been generally accepted in all high function contexts, in particular in schools, that learners (and probably even teachers) do not know these varieties effectively (that is, they do not have the required communicative competency in them) and that they are consequently not used effectively. That is: although considerable corpus development has been undertaken, status, acquisition and usage development still needs to take place to the required extent. As evidence of this, one can take note of the disagreements at the 2005 workshop about the relative roles of rural and urban varieties of the Bantu languages and the degree to which urban ways of speaking (for example Zulu in Soweto) should receive recognition as part of the standard.
Keywords: African Research